The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s12185-017-2270-9
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of mogamulizumab in patients with adult T-cell leukemia–lymphoma in Japan: interim results of postmarketing all-case surveillance

Abstract: We present the interim results of a postmarketing all-case surveillance study in patients with C-C chemokine receptor 4 (CCR4)-positive, relapsed or refractory adult T-cell leukemia-lymphoma (ATL) treated with the anti-CCR4 monoclonal antibody mogamulizumab since its 2012 launch in Japan. The safety and efficacy analysis populations comprised 484 and 442 patients, respectively. The ATL subtype was acute in 58.9% and lymphoma in 34.2% of patients. All patients were scheduled to receive intravenous infusions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 34 publications
2
27
0
Order By: Relevance
“…In fact, we observed that 7 patients died of GVHD among 49 patients who received mogamulizumab before allogeneic HSCT. Our previous result had demonstrated that the rate of grade III‐IV acute GVHD was 28.6% and might be higher compared with that of HSCT not preceded by mogamulizumab, suggesting the risk of severe GVHD is increased by administering mogamulizumab before allogeneic HSCT in patients with ATL . However, it should be paid attention to be led by a small number of patients who have many background factors.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…In fact, we observed that 7 patients died of GVHD among 49 patients who received mogamulizumab before allogeneic HSCT. Our previous result had demonstrated that the rate of grade III‐IV acute GVHD was 28.6% and might be higher compared with that of HSCT not preceded by mogamulizumab, suggesting the risk of severe GVHD is increased by administering mogamulizumab before allogeneic HSCT in patients with ATL . However, it should be paid attention to be led by a small number of patients who have many background factors.…”
Section: Discussionsupporting
confidence: 84%
“…The safety profile reported in this surveillance study was similar to that reported in our preliminary report and in previous clinical trials . IRRs, skin disorders, and infections which were collected as mandatory items were the most common ADRs, and the frequencies for the first two events were less than those reported in the clinical study of patients with relapsed ATL using the same administration schedule of mogamulizumab as used in this surveillance .…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations